Effect of Glycidyl Methacrylate on Water Absorption Properties of Sago Hampas Biocomposite - Mohd Syahmi, Jamaludin; A., Zulkharnain; A.A., Khan; N., Wagiman (UNIMAS Publisher, 2015)
This study examines the water absorption of sago hampas biocomposite utilizing glycidyl methacrylate as its matrix. Composites were fabricated with 25, 30, 40 wt% sago hampas content and another sample of pure sago hampas using hydraulics hot press machine. The water absorption properties of composites with different sago hampas composition were investigated according to Standard Test Method for Tensile Properties of Polymer Matrix Composite Materials of ASTM D570. Water absorption of pure sago hampas composite have the highest average water absorption percentage with 59.1 wt% as compared to the lowest average water absorption percentage recorded for 30 wt% sago hampas content biocomposite with 16.8%. However sago hampas loading was increased resulting in the increased in average water absorption on biocomposite for 40 wt% sago hampas content which is 33.1%.